A Case of Relapsing Polychondritis with Tracheobronchial Involvement - Gurung, Naresh; Shrestha, Ashish; Karthak, Ashish; Shrestha, Sanjeet Krishna; Lama, Rakesh; Bhattarai, Sanjeet; Shrestha, Utsav Kumar; khatri, Sagun (Journal of Advances in Internal Medicine, 2023)
Relapsing Polychondritis (RPC) is a rare systemic inflammatory disorder of unknown etiology and characterized by recurrent and progressive inflammation of the cartilaginous structures, particularly involving the auricles, nose and respiratory tract as well as extra-cartilaginous tissues, including eyes, heart, skin, central nervous and hematological systems. Its diagnosis can be difficult when the typical clinical features such as auricular chondritis are absent. Here, we report on a case of 43-year-old woman who presented with recurrent sore thorat, dysphagia, extertional dyspnea, cough and noisy breathing initially misdiagnosed as acute laryngitis who was eventually diagnosed as Relapsing polychondritis with tracheobronchial involvement. Chest computed tomography showed the diffuse involvement of tracheobronchial cartilage. Based on the, Damiani’s criteria, she was diagnosed as relapsing polychondritis even though there was no unique involvement of auricular cartilage, and high dose steroid and immunosuppressive therapy were then started. This case indicated that patients who have tracheobronchial cartilage involvement without definite auricular chondritis should be considered for relapsing polychondritis as a differential diagnosis. This case is reported to raise awareness of airway involvement in RPC and discuss its current management.